2005
DOI: 10.1038/sj.bjc.6602483
|View full text |Cite
|
Sign up to set email alerts
|

Blockage of angiotensin II type I receptor decreases the synthesis of growth factors and induces apoptosis in C6 cultured cells and C6 rat glioma

Abstract: Angiotensin II (Ang II) is a main effector peptide in the renin -angiotensin system and participates in the regulation of vascular tone. It also has a role in the expression of growth factors that induce neovascularisation which is closely associated to the growth of malignant gliomas. We have shown that the selective blockage of the AT 1 receptor of angiotensin inhibites tumour growth, cell proliferation and angiogenesis of C6 rat glioma. The aim of this study was to study the effects of the blockage of AT 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
83
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(88 citation statements)
references
References 55 publications
3
83
0
2
Order By: Relevance
“…In this respect, ACE inhibitors and angiotensin II receptor blockers (ARBs) have recently acquired an increasing interest as chemopreventive agents [110,117,118] . Of note, ARBs have been associated with reduced cancer occurrence in patients with essential hypertension and a longer exposure to ARBs has been related with major benefits in cancer patients [119] .…”
Section: Gpcrs Activated By Hormonesmentioning
confidence: 99%
“…In this respect, ACE inhibitors and angiotensin II receptor blockers (ARBs) have recently acquired an increasing interest as chemopreventive agents [110,117,118] . Of note, ARBs have been associated with reduced cancer occurrence in patients with essential hypertension and a longer exposure to ARBs has been related with major benefits in cancer patients [119] .…”
Section: Gpcrs Activated By Hormonesmentioning
confidence: 99%
“…ACE is preferentially expressed in PDAC (Arafat et al 2007), and ACE exerts an important role in the occurrence of PDAC through the formation of ANG II. Evidence for the involvement of the ACE-ANG II-AT1R pathway in the pathogenesis of PDAC, such as growth, metastasis, and angiogenesis, has accumulated in recent reports (Egami et al 2003;Arrieta et al 2005).…”
mentioning
confidence: 99%
“…Likewise, the presence of AT1 and AT2 in C6 glioma cells has been described, showing that their blockage can inhibit tumoral growth and angiogenesis (Rivera et al, 2001;Fogarty et al, 2002;Arrieta et al, 2005). Recent reports describe the local expression of many components of RAAS in several human neoplasms, among these human GM (Deshayes and Nahmias, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports, the presence of AT1 was documented in rat astrocytoma cells (Fogarty et al, 2002). Our group has also shown that selective blockage of AT1 inhibits tumour growth, cell proliferation, and angiogenesis by inducing apoptosis in C6 rat malignant glioma (Arrieta et al, 2005), suggesting that AT1 plays a significant role in tumour angiogenesis and growth. In this study, we show the expression of ANGII receptors and their participation in the prognosis of patients with astrocytomas.…”
mentioning
confidence: 95%